The Effect of The Role Playing Model on Student Learning Outcomes of SMP Negeri 2 Wundulako - Ernawati Ernawati; Saparuddin Saparuddin; Alwatia Alwatia (Journal of Biological Science and Education, 2022)
The learning process in class still uses a lot of methods conventional and is less creative in conveying material, namely the model has not been applied one of the innovative learning models is the STAD learning model. The research purpose is to determine the effect of the STAD cooperative learning model on student learning outcomes of SMP Negeri 2 Wundulako. This type of research is quasi-experimental. This research was quantitative. The population in this research were all students of class VIII SMP Negeri 2 Wundulako, amounting to 56 people. The sampling of this research used the purposive sampling technique with certain considerations that each class has the same initial cognitive ability. As the experimental unit, there were two research classes, namely one experimental class and one control class, each of which was 28 people. The data was collected using non-test techniques, observation sheets for student learning activities, and tests in the form of multiple-choice pretest-posttest questions. Then analyzed by descriptive statistic analysis and inferential static analysis. The results of the research inferentially on student learning outcomes using the Independent sample t-test at the significance level = 0.05, obtained t count 8.799 and t table 1.674 because t count ≥ t table, indicating that H0 was rejected and H1 was accepted. It could be concluded that the application of the role-playing model to the digestive system material affected the learning outcomes of class VIII students of SMP Negeri 2 Wundulako.   Keywords:  Role playing model, Student learning outcomes